2006
DOI: 10.1038/sj.ki.5001865
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of hemodialysis on cytokine transcription profiles: Evidence for C-reactive protein-dependency of mediator induction

Abstract: Chronic microinflammation increases cardiovascular morbidity in chronic hemodialysis (HD) patients. Previously published studies are controversial with respect to acute effects of HD treatment on up- or downregulation of cytokine protein levels. Twenty-nine chronic HD patients were hemodialysed for 4 h with a 4008 dialyser using high-flux membranes. Patients were separated into a low (up to 1 mg/dl) and a high (1.1 to 5.5 mg/dl) C-reactive protein (CRP) group. Blood was drawn before HD and 240 min after initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 36 publications
4
32
0
4
Order By: Relevance
“…41,42 We found that hemodialysis increased the concentrations of these cytokines and chemokines, consistent with previously published reports by our laboratory and others. 6,7 That bradykinin B 2 receptor blockade attenuated the rise in MCP-1 after hemodialysis concurs with data from cell culture studies. Thus, bradykinin stimulates lung fibroblasts, type II alveolar cells, macrophages, and bronchial epithelial cells to release inflammatory cytokines and chemotactic factors such as MCP-1, whereas B 2 receptor antagonism decreases cytokine-induced neutrophil migration.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…41,42 We found that hemodialysis increased the concentrations of these cytokines and chemokines, consistent with previously published reports by our laboratory and others. 6,7 That bradykinin B 2 receptor blockade attenuated the rise in MCP-1 after hemodialysis concurs with data from cell culture studies. Thus, bradykinin stimulates lung fibroblasts, type II alveolar cells, macrophages, and bronchial epithelial cells to release inflammatory cytokines and chemotactic factors such as MCP-1, whereas B 2 receptor antagonism decreases cytokine-induced neutrophil migration.…”
Section: Discussionsupporting
confidence: 66%
“…5 For example, hemodialysis increases leukocyte expression of interleukin (IL)-1␤, IL-8, and TNF-␣, and circulating concentrations of IL-6. 6,7 Increased inflammation may, in turn, contrib-ute to derangements of the fibrinolytic system in CHD patients. Cytokines such as TNF-␣, IL-1␤, and IL-6 stimulate expression of plasminogen activator inhibitor-1 (PAI-1), the major physiologic inhibitor of fibrinolysis in vivo.…”
mentioning
confidence: 99%
“…However, in one study, it has been observed that acute transcription of anti-inflammatory cytokines following HD was significantly lower in patients with high serum CRP levels. 36 In contrast, transcription of proinflammatory cytokines (including IL-1␤ and TNF-␣) was induced in equal concentrations, regardless of baseline CRP levels. IL-1␤ and TNF-␣ are known to induce expression of the CCR5 ligands CCL4 and CCL5 in renal disease.…”
Section: Discussionmentioning
confidence: 96%
“…The etiology of inflammation is complex and includes underlying uremia and the continuous contact between blood and dialyzer/dialysate. Indeed, the hemodialysis procedure results in increased leukocyte transcript levels of many proinflammatory cytokines 13 and circulating cytokines increase and remain high at least 2 hours after the end of dialysis. 12 In our study, valsartan and ramipril reduced the levels of IL-6 and IL-8 during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Hemodialysis induces an acute increase in white blood cellular transcription and circulating concentrations of inflammatory markers. 12,13 Inflammatory cytokines, in turn, increase the expression of prothrombotic factors, such as plasminogen activator inhibitor-1 (PAI-1), 14 the major inhibitor of fibrinolysis by inactivating the tissue plasminogen activator (tPA). Increased PAI-1 antigen levels and activity in MHD patients correlate with increased risk of coronary artery disease.…”
mentioning
confidence: 99%